Find the area of the following circle r=9 yd

Answers

Answer 1
Answer: The area of the circle is given by the formula A=pi*r^2 if the radius is 9yd you can simply sub it into the formula. A=pi*9^2 which then becomes A=pi*81 you can then put this into your calculator and you get approximately A=254.469 yds if you are not allowed a calculator use pi as 3.14 A=3.14*81 which gives you 254.34yds (close enough). Hope this helps
Answer 2
Answer:

Answer:

254.34

Step-by-step explanation:


Related Questions

25 POINTS AND BRAINLIESTSUPER EASY!Which is the best scale to use when making a line graph for the data below? Week1234Profits (in dollars)228367385280A) from 0 to 1000B) from 200 to 1000C) from 0 to 400D) from 200 to 400
90 < x < 180 is my range and my answer is 0.6 for it to be correct is it positive or negative?
Which is the volume of a cylinder with a radius of 6 feet and a height of 10 feet? (Use 3.14 for .) A. 1,129.88 cubic feet B. 1,130.40 cubic feet C. 1,130.24 cubic feet D. 1,131.00 cubic feet
Can anyone help? i dont understand math :(
It cost $46 to rent a bike for n days. which expression represent the cost for one day.is it: A. $46 divided by n B. $46 + n C. $46 times n D. n - $46

Given: ∠A and ∠B are complementary angles. m∠A=3x+105 ; m∠B=−6x−39 Prove: m∠B=9° Drag and drop reasons into the boxes to correctly complete the proof. Statement Reason ∠A and ∠B are complementary angles. Given
m∠A=3x+105 ; m∠B=−6x−39 Given
m∠A+m∠B=90° Definition of complementary angles
3x+105−6x−39=90 Substitution Property of Equality
−3x+105−39=90 Simplify.
−3x+66=90 Simplify.
−3x=24
 x=−8
 m∠B=−6(−8)−39
 m∠B=48−39 Simplify.
m∠B=9°

Answers

Answer:

Statement: -3x=90-66

Reason: By subtraction property of equality..

Statement: -3x=24

Reason: By simplification.

Statement: x=(24)/(-3)

Reason: By division property of equality.

Statement: m\angle B= -6(-8)-39

Reason: By substitution property of equality.

Statement: m\angle B=9^(\circ)

Reason: By simplification.

Step-by-step explanation:

Given \angle A and \angle B are complementary angles.

m\angle A= 3x+105

m\angle B=-6x-39

To prove that m\angle B=9^(\circ)

Proof:

1.Statement:\angle A\; and\; \angle B are complementary angles .

Reason: Given .

2.Statement:  m\angle A=3x+105; m\angle B= -6x-39

Reason: Given .

3. Statement: m\angle A+ m\angle B=90^(\circ)

Reason: By definition of complementary angles.

4.Statement:3x+105-6x-39=90

Reason: By substitution  property of equality.

5. Statement: -3x+105-39=90

Reason: By simplification.

6. Statement:  -3x+66=90

Reason: By simplification.

7. Statement: -3x= 90-66

Reason: By subtraction property of equality .

8.Statement:-3x=24

Reason: By simplification.

9.Statement: x=(24)/(-3)

Reason : By division property of equality.

10. Statement: x=-8

Reason: By simplification.

11. Statement: m\angle B= -6(-8)-39

Reason : By substitution property of equality.

12. Statement: m\angle B= 48-39

Reason: By simplification.

13. Statement: m\angle B=9^(\circ)

Reason : By simplification.

Hence, m\angle B= 9^(\circ)

Hence proved.

Given:\angle A and \angle B are complementary angles.

m \angle A = 3x+105^\circ and m \angle B = -6x-39^\circ.

To prove: m \angle B = 9^\circ

Proof:

Statement 1:\angle A and \angle B are complementary angles.

Reason 1: Given

Statement 2:m \angle A = 3x+105^\circ and m \angle B = -6x-39^\circ.

Reason 2: Given

Statement 3:m \angle A + m \angle B = 90^\circ

Reason 3: Definition of complementary angles.

Statement 4:3x+105^\circ -6x -39^\circ = 90^\circ

Reason 4: Substitution property of equality

Statement 5:-3x+105^\circ-39^\circ = 90^\circ

Reason 5: Simplification

Statement 6:-3x+66^\circ = 90^\circ

Reason 6: Simplification

Statement 7:-3x = 24^\circ

Reason 7:  Simplification

Statement 8:x = -8

Reason 8: Multiplication property of equality

Statement 9:m \angle B = -6(-8) - 39^\circ

Reason 9: Substituting the value of 'x'

Statement 10:m \angle B = 48-39 = 9^\circ

Reason 10: Simplification


Kevin, Conner, and John each walk several miles per day as part of a fitness program. Kevin walks 3 miles less than Conner, and John walks 2 miles more than Conner does. Over 3 days the difference between the number John and Kevin walk is equal to one half the number of miles that Conner walks. How many miles does each person walk each day?

Answers

Answer:

The distance Conner walks each day is 10 miles

The distance Kevin walks each day is 7 miles

The distance John walks each day is 12 miles

Step-by-step explanation:

The question is a word problem

Let the number of miles Conner walks per day = x

The given inforf the totmation in the question are;

The distance Kevin walks per day = x - 3 miles

The distance John walks per day = x + 2 miles

In three days, the difference between the total distance John walks and the total distance Kevin walks is equal to half the total distance Conner walks

The number of miles each person walks per day is found as follows;

3×(x + 2) - 3×(x - 3) = 3·x/2

3·x + 6 - 3·x - (-9) = 3·x/2

3·x + 6 - 3·x + 9 = 3·x/2

3·x - 3·x + 6  + 9 = 3·x/2

0 + 6  + 9 = 3·x/2

15 = 3·x/2

x = 15×2/3 = 10 miles

x = 10 miles

Therefore, the distance Conner walks each day = 10 miles

The distance Kevin walks per day = (x - 3) miles = (10 - 3) miles = 7 miles

The distance Kevin walks per day = 7 miles

The distance John walks per day = (x + 2) miles = (10 + 2) miles = 12 miles

The distance John walks per day = 12 miles.

Explain one thing you need to be careful with when writing a proportion.

Answers

For this case, we have that by definition, the proportions can be expressed in different ways. Example, if we have a dog and three cats:

75%: It's percentage

0.75: In decimal (75% are cats)

\frac {3} {4}: In fraction. (There are \frac {3} {4} of cats)

3: 1: Using ":" to separate sample values. (For every three cats there is a dog)

Care should be taken with the proportions, always multiplying the numbers in the proportion by the same value.

Example:3: 1 = 3 * 2: 1 * 2 = 6: 2

Answer:

Care should be taken with the proportions, always multiplying the numbers in the proportion by the same value.

The sum of two numbers are 62 and the difference is 18. Wjat are the numbers

Answers

The numbers are 40 and 22.

What is an expression?

An expression is a way of writing a statement with more than two variables or numbers with operations such as addition, subtraction, multiplication, and division.

Example: 2 + 3x + 4y = 7 is an expression.

We have,

Let the numbers be m and n.

The two expressions are:

m + n = 62 ______(1)

m = 62 - n ______(2)

m - n = 18 ______(3)

From (2) and (3)

(62 - n) - n = 18

62 - n - n = 18

62 - 2n = 18

62 - 18 = 2n

n = 44/2

n = 22

Now,

m + n = 62

m = 62 - 22

m = 40

Thus,

m = 40 and n = 22.

Learn more about expressions here:

brainly.com/question/3118662

#SPJ3

let the two numbers be x and y, then

x + y = 62 . . . . . . . (1)
x - y = 18 . . . . . . . .(2)

subtracting (2) from (1), we have:

2y = 44
y = 22

From (2), x + 22 = 62
x = 62 - 22 = 40

therefore, the two numbers are 40 and 22.

If point A is between B and C then BA + AC = BC. always sometimes never

Answers

Always

Anytime point A is on line BC, AB+BC=BC

The answer is Always

Step-by-step explanation:

What adds up to 11 and multiplies to -80

Answers

let your number be x

your equation will be (x+11)x = -80
expand the equation x^2 +11x +80 = 0
solve the equation and find x
its +16 and -5.
+16+-5= 11
+16*-5=-80